2014
DOI: 10.1002/sat.1071
|View full text |Cite
|
Sign up to set email alerts
|

A modified rain attenuation prediction model for tropical V‐band satellite earth link

Abstract: SUMMARY Radio wave propagation plays a very important part in the design and eventually dictates performance of space communication systems. Over time, the requirements of satellite communication have grown extensively where higher capacity communications systems are needed. Escalating demands of microwave and millimetre wave communications are causing frequency spectrum congestion. Hence, existing and future satellite system operators are planning to employ frequency bands well above 10 GHz. The challenge in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Sharan presented work regarding the prediction of rainfall based on an average of three methods where the historical rain data of Bihar were selected for projection and found that the predicted results were quite close to the actual rainfall data for 2013 [23]. Many other researchers have shown that rain is predictable and this information can be used in many applications [24,25].…”
Section: Related Workmentioning
confidence: 99%
“…Sharan presented work regarding the prediction of rainfall based on an average of three methods where the historical rain data of Bihar were selected for projection and found that the predicted results were quite close to the actual rainfall data for 2013 [23]. Many other researchers have shown that rain is predictable and this information can be used in many applications [24,25].…”
Section: Related Workmentioning
confidence: 99%
“…To transform the rainfall rate into rain attenuation , ITU‐R recommendation P.618‐12 is followed using a frequency of 22 GHz (the highest frequency in the 21.4–22 GHz band which is allocated next satellite broadcasting in ITU region 1 and 3). The rainfall rate exceeded at 0.01% of the time is used for predicting the rain attenuation value.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The proper scaling mechanism regarding these parameters is yet to be devised. The ITU-R model is the most significant model that has been moderated for tropical regions by many researchers [29,[142][143][144][145][146]. However, these models do not support the scaling properties.…”
Section: Scaling Improvementmentioning
confidence: 99%